Gender Equality in Sports ? does the state have responsibilities? - Bjarnadóttir, María Rún; Magnússon, Bjarni Már; Kristjánsdóttir, Hafrún; Guðmundsdóttir, Margrét Lilja (Stjórnsýslustofnun, 2018)
The article is the first to explore the Icelandic legal framework for sports with a focus on gender equality. The underlying principles of the current legal framework, domestic and international obligations as well as government policy and funding are analyzed, applying doctrinal methodology. Due to the structural formation of sports in Iceland, the article also examines the Icelandic sports association and to what extent gendered perspectives are reflected in its structure, bylaws and policy. The main conclusion is that the state does have an obligation to ensure gender equality in sports in Iceland. The article suggests some legal uncertainty as regards the extent of this responsibility, not least due to the distributed structure of legal responsibility of sports in Iceland. The distinction between sports as an organized recreational or youth activity on one hand and as a part of the work market on the other, calls for further studies concerning recent legal amendments demanding equal pay for equal work under the Gender Equality Act. The findings of the article highlight that there is room for improvement concerning the promotion of gender equality in Icelandic sports. The authors suggest a number of efforts for public authorities and the sports movement in Iceland to improve the situation. Í greininni er lagalegt umhverfi íþrótta á Íslandi kannað með hliðsjón af kynjajafnréttissjónarmiðum með hinni fræðilegu lagalegu aðferð (e. doctrinal method). Þannig eru skoðuð sjónarmið sem legið hafa til grundvallar lagasetningu um íþróttir, innlendar og alþjóðlegar skuldbindingar íslenskra stjórnvalda og rýnt í hvort jafnréttissjónarmiða gæti í stefnumótun og fjárútlátum stjórnvalda í íþróttamálum. Í ljósi lögbundins hlutverks íslensku íþróttahreyfingarinnar er inntak hennar og uppbygging skoðuð með hliðsjón af sömu sjónarmiðum. Niðurstöður rannsóknarinnar eru að ríkið er skuldbundið til þess að tryggja kynjajafnrétti í íþróttum. Inntak þeirrar skuldbindingar er þó að einhverju leyti óskýrt. Lagaleg ábyrgð á ...